First randomized trial on clobetasol propionate and mometasone furoate in the treatment of vulvar lichen sclerosus: results of efficacy and tolerability. (1st August 2014) - Virgili, A.; Borghi, A.; Toni, G.; Minghetti, S.; Corazza, M.
Summary: Background: A 3‐month topical application of clobetasol propionate (CP) represents the recommended and accepted first‐line treatment for vulvar lichen sclerosus (VLS); however, to date, no randomized controlled trials have compared the efficacy and safety of CP with other topical corticosteroids. Objective: To compare the effectiveness and tolerability of two different topical corticosteroids, CP 0·05% ointment and mometasone furoate (MMF) 0·1% ointment, in the treatment of VLS. Methods: Fifty‐four patients with VLS were enrolled in a 12‐week active treatment phase (ATP) and randomized to apply either CP or MMF in a tapering regimen. The main efficacy parameters were the response rate, the rate of patients achieving an improvement from baseline of ≥ 75% in the subjective and objective scores, and the mean reduction in subjective and objective scores throughout the treatment. Results: By the end of the 12‐week ATP, 24 (89%) patients were considered to be responders among the CP patients and 24 (89%) among the MMF patients; 59% and 37% of patients in the CP group and 67% and 48% in the MMF group achieved an improvement of at least 75% in subjective and objective scores, respectively. The decrease in mean symptom and sign scores was significant compared with baseline with both treatments. No significant differences were found in any of the assessed efficacy endpoints between CP and MMF. Both treatments were well tolerated. Conclusions: Clobetasol propionate and MMF appeared similarly efficacious and well tolerated for the treatment of VLS and both may represent the first‐line treatment for the disease.